PEMBENTUKAN IDENTITAS BARU TOKOH IMIGRAN DALAM EMPAT CERPEN KARYA DUA PENGARANG BERLATAR BELAKANG IMIGRAN WLADIMIR KAMINER DAN DILEK GÃ¼NGÓ§R - Hawa, Andina Meutia; Rahayu, Lina Meilinawati; Purnomowulan, N. Rinaju (ATAVISME, 2017)
This research aims to reveal the depiction of formation of the new identity of immigrant characters in four short stories written by two immigrant authors in contemporary German literature, Wladimir Kaminer and Dilek Güng?r. This study discusses how the immigrant characters build their new identities and their self-subjectivities in four short stories, namely ?Schlechte Vorbilder?, ?Deutsch-russisch Kulturjahr?,  "Geld oder Leben? and ?Blondes Barbie?. This study applies Hall?s (1990) identity theory and Bhabha?s (1994) hybridity theory. This study uses the qualitative approach with the descriptive-analytics method. The result of this study argues that the identity formation of immigrant characters is performed by imitating other cultures and presenting the past memory of the immigrant characters in their present lives as an effort to liberate the immigrant characters from their otherness and to build their self-subjectivities. In addition, the depiction of formation of the immigrant characters? new identities also shows that identity is a fluid concept, and a means of rejection of the two immigrant authors towards the essentialism concept of identity.